Description of Parents' Attention to Child Learning Outcomes in RW 10 Kelurahan Korong Gadang Kecamatan Kuranji Kota Padang - Elsa Andriyani; Syafruddin Wahid; Vevi Sunarti (Universitas Negeri Padang, 2019)
The background of this study by increasing child learning outcomes at RW 10 Kelurahan Gadang, Kuranji, Padang City. The purpose of this study is to describe parents’ attention towards children's learning outcomes in receiving children present, given children's behavior, providing learning opportunities and learning equipment for children, showing positive expectations. The type of this study is descriptive quantitative, the population in this study are students class VIII, and IX Junior High School at 10 Korong Gadang, Padang City. which amounts to thirty-one people. Twenty-two samples using the stratified random sampling technique. The technique of collecting data is a questionnaire and a data collection tool is an approved list. Data analysis techniques use percentage calculations. Children show positive expectations categorized as very good. Suggestions in this study are expected for parents to increase attention to the learning process.Keywords: Parents’ Attention, Child Learning Outcomes